Enhanced CMAS and hot corrosion degradation of YSZ thermal barrier coating with nano powders - ÖZÇELİK, Abdulkadir; AKDOĞAN EKER, Ayşegül; KARABAŞ, Muhammet; AVCI, Ali; KÜÇÜKYILDIRIM, Bedri Onur (Surface & coatings technology, 2024)
Thermal barrier coatings are used to protect hot section parts of gas turbine engines. These coatings are subject to corrosion due to impurity elements in the fuel and dust absorbed from the atmosphere into the engine. The rough and porous surface nature of plasma-sprayed coatings facilitates the penetration of these factors into the coating. Coatings are damaged prematurely as a result of corrosion. In this study, nano-structure YSZ, YSZ + Al2O3, YSZ + TiO2, and YSZ + Al2O3 + TiO2 coatings were deposited on plasma sprayed YSZ coating by electrophoretic deposition method. Hot corrosion and CMAS resistance were investigated. The coatings were characterized by SEM, XRD, AFM, and microhardness before corrosion tests. The changes in the coatings after corrosion tests were characterized by SEM and XRD. The penetration behavior of corrosive factors was examined by elemental mapping with EDS. Nanostructure coatings deposited on APS YSZ made the surfaces of as-sprayed coatings more stable. The ability of these nanolayers to prevent pure penetration into coatings during hot corrosion and CMAS is limited. However, the Al2O3 + TiO2-doped nanostructure YSZ reduced the bond-layer oxidation. In addition, the addition of Al2O3 + TiO2 to the EPD deposited layer also reduced the tetragonal-monoclinic phase transformation that occurred in YSZ as a result of corrosion. Al2O3 and TiO2 additives alone are not effective in improving the corrosion behavior of coatings. Nanostructured coatings deposited with the EPD technique can help protect plasma-sprayed thermal barrier coatings against corrosion. •Approximately 20 μm thick nanostructured coatings were successfully deposited on plasma-sprayed YSZ using the EPD method•Surface porosities in plasma sprayed coating are eliminated. Surface roughness has been reduced.•In hot corrosion and CMAS corrosion tests, the least pure penetration was obtained in Al2O3+TiO2 doped nano YSZ.•Nanostructured coatings deposited with the EPD technique have great potential in protecting APS TBC against corrosion